2019
DOI: 10.1074/jbc.ra118.007135
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a murine cell line for the stable propagation of hamster prions

Abstract: Edited by Ursula Jakob Prions are infectious protein aggregates that cause several fatal neurodegenerative diseases. Prion research has been hindered by a lack of cellular paradigms for studying the replication of prions from different species. Although hamster prions have been widely used to study prion replication in animals and within in vitro amplification systems, they have proved challenging to propagate in cultured cells. Because the murine catecholaminergic cell line CAD5 is susceptible to a diverse ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 72 publications
1
38
0
Order By: Relevance
“…Even though “promiscuous” PrPs like bank vole PrP are suitable for a range of prions, they may not necessarily provide optimum infectivity as was observed here with MEF cells. Very recently, the successful engineering of CAD5 cells for the stable propagation of hamster prions was shown 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though “promiscuous” PrPs like bank vole PrP are suitable for a range of prions, they may not necessarily provide optimum infectivity as was observed here with MEF cells. Very recently, the successful engineering of CAD5 cells for the stable propagation of hamster prions was shown 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these were mostly established cell lines that allowed persistent propagation of mouse-adapted scrapie prion strains like 22L, RML, or ME7 ( 24 , 25 ). By using genetically engineered cells, it seems possible to expand the range of prions which can be propagated in such cell lines ( 26 28 ). There still is no cell line that can persistently propagate human or bovine prions ( 25 ).…”
mentioning
confidence: 99%
“…These bvCAD5 cells could also be infected with 22L prions [ 33 ]. Additionally, Bourkas et al, demonstrated that CAD5 cells expressing hamster PrP could propagate the 263K, hyper (HY) and 139H strains of hamster-adapted prions, but not the drowsy (DY) strain [ 32 ]. Thus, CRISPR has proven to be a useful tool for investigating species barriers.…”
Section: Immortalized Cell Linesmentioning
confidence: 99%